DETERMINATION OF FLEXIBILITY IN ELDERLY WOMEN FROM THREE DIFFERENT PROTOCOLS (Fiep Bulletin - online, 2015)
The aging process is associated with a number of morphological and functional, including the decrease in many important components of physical fitness, such as flexibility. This functional reduction compromises the realization of a number of daily living activities. The objective of this study was to determine the levels of flexibility from three distinguish flexibility protocols. Participated of this study 927 women, non-institutionalized, older than 60 years, divided in five age groups AG 1 (6064 years; n = 277), AG 2 (6569 years; n = 283), AG 3 (7074 years; n = 202), AG 4 (7579 years; n = 114) and AG 5 (>80 years, n= 51). Flexibility was measured using the Sit-and-Reach Test (SR) (WELLS and DILLON,1952); Chair Sit-and-Reach Test (CSR) (RIKLI and JONES,1999); and the movements of shoulder adduction (SA), hip flexion (HF) and hip abduction (HA) were accessed according to the norms of utilization of the instrument inclinometer (INC) (ACHOUR, 2004). The gradual decrease of flexibility was observed in all tests. The Shoulder Abduction movement and the Hip Flexion movement reduced 7.3% and 5.2% respectively and  this reduction was more pronounced on the Hip Abduction which declined 23.6%. There were no differences in changes of flexibility between right and left hemi-bodies. There was an association among all age groups and the tests that measured hip mobility, being r=0.621, 0.556 and 0.697 for the 60-64 age group; r=0.578, 0.456 and 0,742 for the 65-69 age group; r=0.409, 0.367 and 0.725 for the 70-74 age group, r=0.540, 0.496 and 0.809 for the 75-79 age group and, r=0.533, 0.519 and 0.729 for the >80 age group among HF and SR, HF and CSR, and SR and CSR, respectively (p
Keywords: aging; flexibility.